A produção do sujeito musical campeiro na vertente da canção nativista estudantil em Santana do Livramento - RS - Larruscain, Edilacir dos Santos (2012)
This dissertation presents discursive practices that produce the Countryman Musical Subject, a type of subjectivity of gauchismo of Rio Grande do Sul, which circulates in the Student Nativist Song Branch, a music festival which has been gathering, since 2002, at Liberato Salzano Vieira da Cunha Public School, in Santana do Livramento-RS, hundreds of students from Basic Education up to universities from that city and neighboring towns. The work is an ethnographic study and is linked to the Line of Research and Education and Arts-LP4 and to the research group DEC-Difference, Education and Culture, of the Post-Graduation Program in Education of the Federal University of Santa Maria. The Branch is considered, in this study, as a cultural teaching instance, where subjects immersed in relations of powerknowledge, based on Nativist Gaucho culture. Taking into consideration the approach from the Cultural Studies in Education, which understands culture as a set of significant systems that generate knowledge and constitute subjectivities, it is analyzed the circulation of narratives that spell out the production of the Countryman Musical Subject, a kind of subjectivity aligned to the musical practices of nativist discourses, embedded in the overall production and consumption of cultural goods. In the text, there is a description of markers of gaucho culture that produce Countryman Musical Subject, and from the narratives of Music workshops as well as teachers and students of the organizing committee of the festival. It is analyzed the experience of production of subjectivities of students and teachers participating in Nativist Song Branch.